Investigating students’ common errors in integers - Badarudin, Bny Rosmah; Khalid, Madihah (Education Technology Centre, Universiti Brunei Darussalam, 2009)
Integers can be considered as another topic in mathematics which students find to be difficult. Students make mistake and get confused with signs and operations when solving routine problems involving operations with integers. This paper reports on the investigation into Bruneian Form One pupils’ error on integer operations. In July 2006, 149 pupils from a secondary school were given a pencil-and-paper test to rest their knowledge on integers. These questions involved routine addition, subtraction, multiplication, division and mixed operation computation. The analysis of their vest paper showed that pupils tend to make certain errors that are common and for a common reason. Thus the percentages of pupils making some particular errors were calculated and the errors were classified into certain categories. Some students were also interviewed to determine and confirm their reasons for making these errors.